Screening of potential key ferroptosis-related genes in Chronic Obstructive Pulmonary Disease - Cao Y; Pan H; Yang Y; Zhou J; Zhang G (International Journal of COPD, 2023)
Yumeng Cao,1,* Huaqin Pan,2,* Yanwei Yang,3 Jingrun Zhou,1 Guqin Zhang1 1Department of Respiratory and Critical Care Medicine, Zhongnan Hospital of Wuhan University, Wuhan, Hubei, 430071, People’s Republic of China; 2Transplantation Intensive Care Unit, Transplant Center of Wuhan University, Hubei Key Laboratory of Medical Technology on Transplantation, Wuhan, Hubei, 430071, People’s Republic of China; 3Department of Critical Care Medicine, Zhongnan Hospital of Wuhan University, Wuhan, 430071, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guqin Zhang, Department of Respiratory and Critical Care Medicine, Zhongnan Hospital of Wuhan University, Wuhan, Hubei, 430071, People’s Republic of China, Email zgqxiaoxiao@126.comPurpose: Ferroptosis plays essential roles in the development of COPD. We aim to identify the potential ferroptosis-related genes of COPD through bioinformatics analysis.Methods: The RNA expression profile dataset GSE148004 was obtained from the GEO database. The ferroptosis-related genes were obtained from the FerrDb database. The potential differentially expressed ferroptosis-related genes of COPD were screened by R software. Then, protein–protein interactions (PPI), correlation analysis, gene-ontology (GO) enrichment analysis, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis were applied for the differentially expressed ferroptosis-related genes. Finally, hub gene-microRNA(miRNA), hug gene-transcription factor interaction networks were constructed by miRTarBase v8.0 and JASPAR respectively, and hub gene drugs were predicted by the Enrichr database.Results: A total of 41 differentially expressed ferroptosis-related genes (22 up-regulated genes and 19 down-regulated genes) were identified between 7 COPD patients and 9 healthy controls. The PPI results demonstrated that these ferroptosis-related genes interacted with each other. The GO and KEGG enrichment analyses of differentially expressed ferroptosis-related genes indicated several enriched terms related to ferroptosis, central carbon metabolism in cancer, and the HIF-1 signaling pathway. The crucial miRNAs and drugs associated with the top genes were identified.Conclusion: We identified 41 potential ferroptosis-related genes in COPD through bioinformatics analysis. HIF1A, PPARG, and KRAS may affect the development of COPD by regulating ferroptosis. These results may expand our understanding of COPD and might be useful in the treatment of COPD.Keywords: ferroptosis, COPD, bioinformatics analysis, gene expression omnibus dataset